Control of digital data breach risks in companies as a crucial factor for guarding human right to privacy - Romanova, Jekaterina (Riga Graduate School of Law, 2018)
This thesis studies company data breach as one of the major threats to human rights in the modern age of advanced information technologies and digitalization of operations as a new reality. The thesis argues that the realization of the fact that modern day digital data breaches are a crucial factor to guarding the privacy of individuals and securing the human right to privacy. The research analyzes the existing challenges of the modern age related to the business operation necessity to collect and store big data; studies the risks and consequences, which derive from data collection, loss, theft and misuse.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International private law and international procedural law; Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; Privacy